2016
DOI: 10.18488/journal.58/2016.3.1/58.1.23.27
|View full text |Cite
|
Sign up to set email alerts
|

The Particle Size and Thermal Properties of Flour from three Plantain (Musa Paradisiaca) Cultivars Grown in Nigeria

Abstract: Flour from three plantain cultivars (Agbagba, Cadaba and French horn) commonly grown in Nigeria were investigated for their particle size, bulk density and thermal properties. The results showed that Agbagba cultivar had the least particle size (10.04%) at 125µm sieve size and significantly increased to 29.45% at 180µm sieve size. Cadaba and French horn plantain cultivars showed a particle size of 56.54% and 36.20% at 125µm sieve size, respectively and decreased significantly with increase in sieve sizes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…The finding showed that Cp of anchote flour is similar to that of cocoyam flour (1.744-1.785 kJ/kg o C) (Ajala et al, 2014) and flours of plantain cultivars (1.67-1.7 kJ/kg o C) (Barine & Victor, 2016).…”
Section: Specific Heat Capacity (Cp)mentioning
confidence: 77%
See 3 more Smart Citations
“…The finding showed that Cp of anchote flour is similar to that of cocoyam flour (1.744-1.785 kJ/kg o C) (Ajala et al, 2014) and flours of plantain cultivars (1.67-1.7 kJ/kg o C) (Barine & Victor, 2016).…”
Section: Specific Heat Capacity (Cp)mentioning
confidence: 77%
“…The specific heat capacity was derived from the proximate composition of the samples as per the method described by Barine and Victor (2016) (Equation 4). Cp=4.180Xw+1.711Xp+1.929Xf+1.547Xc+0.908Xawhere Cp is specific heat capacity in KJ/Kg K , and Xs is the respective mass fractions of water ( Xw ), protein ( Xp ), fat ( Xf ), carbohydrate ( Xc ), and ash ( Xa ) present in each sample and obtained from proximate compositions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…°C-1 ] of selected foods[17][18][19], c T is the different temperature of cooking after and before[°C].Third, determine the mass of biomass fuel required bb m ;…”
mentioning
confidence: 99%